Don't let's go to the dogs tonight [videorecording (DVD)] - Fuller, Alexandra, 1969-; Davidtz, Embeth, 1966-; Davidtz, Embeth, 1966-; Venter, Lexi; Bali, Zikhona (Sony Pictures Classics, 2025)
Based on Alexandra Fuller's memoir of the same name, Don't Let's Go To The Dogs Tonight captures the childhood of 8-year-old Bobo on her family farm in Zimbabwe (formerly Rhodesia) at the end of the Zimbabwean War for independence in 1980. Growing up in the midst of this long running war, Bobo internalizes both sides of the struggle. Conflicted by her love for people on opposing sides, she tries to make sense of her life in a magical way. Through her eight-year-old gaze we witness Rhodesia's final days, the family's unbreakable bond with Africa, and the deep scars that war leaves on survivors.